(untitled) (Baghdad Science Journal, 2025)
The present study was investigated the activity of aqueous extract from Cinnamomum cassia bark on the blood glucose levels in healthy and diabetic rats induced by Streptozotcin (STZ). In healthy rats the blood glucose levels were slightly decreased after six hoursof single oral administration with dose (25 mg/kg) of body wight, as well as four weeks after twice daily repeated oral administration of aqueous extract of Cinnamomum cassia bark. In streptozotocin induced diabetic rats we absorved high significant decreased (p